Analisis Daya Solar Cell pada Lampu Parkiran di Bandara Sultan Muhammad Kaharuddin Sumbawa - Pasaribu, Yoga Nugraha Putra; Siregar, Muhammad Fadlan; Hidayat, Jhoni (Lembaga Yasin AlSys, 2024)
This research aims to analyze the condition of parking lights that use renewable energy, namely solar cells. Basically, the condition of the parking lights is not working optimally or not in accordance with the predetermined light on time settings due to the lack of power supplying the parking lights, resulting in a lack of live time for the solar cell parking lights. Data on the equipment module used in the solar cell parking lights is collected and real data in the field or manual measurement data will then be analyzed. The results will be a comparison between the data in the tool module and the measurement data in the field. The impact is the lack of lighting in the parking area of Sumbawa's Sultan Muhammad Kaharuddin Airport. Equipment checking and routine maintenance must be carried out to resolve problems that occur with parking lights. This research provides a better understanding of renewable energy, namely solar cells.